An outdoor test facility for the Cherenkov Telescope Array mirrors - Medina, Maria Clementina (2016)
The Cherenkov Telescopes Array (CTA) is planned to be an Observatory for very high energy γ-ray astronomy and will consist of several tens of telescopes which account for a reﬂective surface of more than 10000 m2 . The mirrors of these telescopes will be formed by a set of facets. Different technological solutions are under test inside the CTA Consortium. Most of them involve composite structures whose behavior under real observing conditions is not yet fully tested. An outdoor test facility has been built in one of the candidate sites for CTA, in Argentina (San Antonio de los Cobres [SAC], 3600m a.s.l) in order to monitor the optical and mechanical properties of these facets exposed to the local atmospheric conditions for a given period of time. In this work we present the preliminary results of the ﬁrst Middle Size Telescope (MST) mirror-monitoring campaign, started in 2013.